2021
DOI: 10.7759/cureus.14257
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Barbed Suture Versus Polyglactin 910 Suture for Vaginal Cuff Closure in Total Laparoscopic Hysterectomy

Abstract: Introduction and objective Laparoscopic suturing of the vaginal cuff and knotting is the most challenging step in total laparoscopic hysterectomy (TLH) and requires surgical skill. The objective of this study was to compare the efficacy and safety of unidirectional barbed suture (V-Loc TM 180; Covidien, Mansfield, MA) with the conventional polyglactin 910 suture (coated Vicryl; Covidien) for vaginal cuff closure in patients with benign uterine diseases undergoing total laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…3 Pooled estimates of suture time [min] and subgroup analysis according to surgery type for the use of VBS versus CS in OB/GYN surgery. Data extracted from references: 8 , 9 , 26 , 29 31 , 37 , 40 , 44 , 47 , 49 …”
Section: Resultsmentioning
confidence: 99%
“…3 Pooled estimates of suture time [min] and subgroup analysis according to surgery type for the use of VBS versus CS in OB/GYN surgery. Data extracted from references: 8 , 9 , 26 , 29 31 , 37 , 40 , 44 , 47 , 49 …”
Section: Resultsmentioning
confidence: 99%
“…Despite the estimated rates of VCD being higher for TLH, including robotic-assisted TLH (RATLH), there are clear benefits to minimally invasive hysterectomies – decreased perioperative complications, decreased blood loss, decreased pain, faster recovery, shorter hospitalization time, and improved patient satisfaction [5,20 ▪ ,21 ▪ ,22 ▪ ]. As VCD is rare overall, the most minimally invasive approach appropriate for the patient should be the chosen method.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
“…A large systemic review and meta-analysis found that barbed suture decreased the risk for VCD in TLH and RATLH but a sub-analysis looking only at TLH did not find a difference in VCD rate between barbed suture and traditional absorbable suture [3 ▪▪ ]. Several studies, including a systemic review and meta-analysis of 11 studies, showed that there was no significant difference in VCD rate when comparing absorbable barbed, traditional absorbable, and/or permanent suture [3 ▪▪ ,6 ▪ ,18,21 ▪ ,32–34]. With this mixed information, surgeons should use the appropriate suture they are most comfortable with.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
See 2 more Smart Citations